Eastern European Cinema - Borjan, Etami (2004)
The lecture was on the new tendencies in the post-communist and post-socialist Eastern European cinemas, with the special focus on the cinemas of the former Yugoslavia, especially Croatian.
Projekt MZOS
ENG